Teaching strategies for the development of listening skills to beginner-level students at unidad educativa Península de Santa Elena peninsula, La Libertad, province of Santa Elena, school year 2021-2022 - Solano Gómez, Ivonne Carolina (2021)
This document is a research project whose objective was to highlight the importance of teaching strategies for the development of listening skills when learning the English language in order to improve the hearing capacity of students. The beneficiaries were 16 ninth-year elementary school students from the Santa Elena Peninsula Educational Unit, in the province of Santa Elena, Ecuador. For the development of this research, the quantitative method was applied, where a survey was carried out to the research group that allowed obtaining specific data about what students really feel and think about the use of teaching strategies to improve their skills in teaching. listens. After the results of the analysis of the survey, it was discovered that for students the application of teaching strategies is very important when learning English, since in this way, they can generate significant effects and notably improve their listening skills in a more effective way. fun and interesting, due to the encouragement and confidence generated by the teacher at the time of applying some type of strategies in the learning environment. Before all of the above, a methodological guide is proposed focused on cognitive strategies, which are responsible for exploiting all the intellectual capacities of students, developing their listening comprehension in a way that is much more focused on this ability.